Influence of silicon on wear behaviour of "silal" cast irons (2014)
The tribological and mechanical properties of various cast irons with different contents of carbon and silicon are studied. The Brinell hardness or every cast iron was measured and their wear resistance was calculated according to ASTM G99 standard, "Standard Test Method for Wear Testing with a Pin-on-Disk Apparatus. These results were related to microstructure, composition and casting processes of the cast irons. The best wear behaviour was experienced by the cast irons with spheroidal graphite and a ferrite matrix in their microstructure. At the same time, the cast irons with the lowest wear resistance are those that have flaky graphite and a purely ferrite matrix in their microstructure. In addition, various casting processes have been tested in order to determine their influence on the appearance of spheroidal graphite.